2016
DOI: 10.1111/jgh.13152
|View full text |Cite
|
Sign up to set email alerts
|

BCLC stage B is a better designation for single large hepatocellular carcinoma than BCLC stage A

Abstract: Patients in group 2 had a worse prognosis than those in group 1 and a similar prognosis to those in group 3. Our results suggest that BCLC stage B is the best stage designation for SLHCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 48 publications
2
40
1
Order By: Relevance
“…This was consistent with the findings of previous studies, which reported patients with SLHCC to have lower 5-year OS rates (36.8–42.9%) than those with BCLC stage A HCC (55.4–58.6%) [16, 17]. Our study further demonstrated that SLHCC patients had an intermediate OS rate between those in the BCLC stages A and B.…”
Section: Discussionsupporting
confidence: 82%
“…This was consistent with the findings of previous studies, which reported patients with SLHCC to have lower 5-year OS rates (36.8–42.9%) than those with BCLC stage A HCC (55.4–58.6%) [16, 17]. Our study further demonstrated that SLHCC patients had an intermediate OS rate between those in the BCLC stages A and B.…”
Section: Discussionsupporting
confidence: 82%
“…Although some studies have reported similar survival between single large HCCs and single small HCCs [25, 26], they were composed of well-selected patients who have received resection. However, most recent studies revealed that solitary large HCC should be classified at least as intermediate stage HCC [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…According to the AJCC (6th) staging manual, BCLC B is equal to parts of stage T3 and C is equal to part of stage T3 and T4, respectively [25]. Currently, patients with BCLC B are generally treated with TACE, and patients with BCLC C are treated with sorafenib alone.…”
Section: Discussionmentioning
confidence: 99%